Health-related quality of life and working conditions on public transport workers in the Metropolitan Region of Belo Horizonte, Brazil, 2012 - Silva, Luiz Sérgio; Assunção, Ada Ávila (Journal of Occupational Health, 2014)
Drivers and conductors working in public transport are frequently exposed to inadequate working conditions and consequently to health problems relating to their work activities. This study investigates the relationship between the working conditions of drivers and conductors in the Metropolitan Region of Belo Horizonte and their perception of health-related quality of life. Health-related quality of life was measured in a sample of 1,607 public transport workers in the city of Belo Horizonte using the SF-12 (Medical Outcomes Study Short-Form General Health Survey). The presence and magnitude of independent associations between the SF-12 domains and the exposure variables were determined by means of odds ratios obtained through logistic regression. After adjustments, the PCS (Physical Component Score) was found to be negatively associated with the existence of breaks during the working day and positively associated with unavailability of technical resources for meeting needs. The MCS (Mental Component Score) was positively associated with being female, having two or more medical diagnoses of illnesses, absenteeism and recent episodes of aggression or threats, and feeling vibration in the whole body. The MCS was negatively associated with the practice of physical exercise. Both components were negatively associated with older age and positively associated with having a poor self-assessment of health. Exposure to a variety of risk factors while performing work worsened health-related quality of life. The results obtained may provide support for rethinking and guiding public policies directed towards metropolitan populations.
Keywords: Health-related quality of life; SF-12; Urban public transport